2022
DOI: 10.1007/s10238-022-00792-6
|View full text |Cite
|
Sign up to set email alerts
|

Toll- like receptor 2 polymorphism and IL-6 profile in relation to disease progression in chronic HBV infection: a case control study in Egyptian patients

Abstract: Chronic hepatitis B (CHB) has a wide range of outcomes depending on host immune responses mainly Toll-like receptors (TLRs) signaling and released cytokines. Toll-like receptor 2 (TLR2) single nucleotide polymorphisms (SNPs) and interleukin 6 (IL-6) may influence the course of CHB. We aimed to elucidate the relation between TLR-2 polymorphism, IL-6 profile, and CHB progression. We analyzed TLR-2 polymorphism (SNP; rs3804099) in 185 CHB patients and 60 controls using TaqMan allelic discrimination assay. Serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Their findings can help anticipate proteinuria and could lead to more personalized treatment for people who have had a kidney transplant. After kidney transplantation, this result suggested that the risk of proteinuria was toughly associated with the rs3804099 (Elbrolosy et al, 2022). Other authors discovered that the rs3804099 SNP has been associated to a number of illnesses, including polycystic ovarian syndrome and H. pylori infection and peptic ulcer, when compared to non-significant SNPs (Filus, Trzmiel, Kuliczkowska-Paksej, Tworowska, & Milewicz, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Their findings can help anticipate proteinuria and could lead to more personalized treatment for people who have had a kidney transplant. After kidney transplantation, this result suggested that the risk of proteinuria was toughly associated with the rs3804099 (Elbrolosy et al, 2022). Other authors discovered that the rs3804099 SNP has been associated to a number of illnesses, including polycystic ovarian syndrome and H. pylori infection and peptic ulcer, when compared to non-significant SNPs (Filus, Trzmiel, Kuliczkowska-Paksej, Tworowska, & Milewicz, 2006).…”
Section: Discussionmentioning
confidence: 96%